MEDIASI SEBAGAI KOMUNIKASI HUKUM DALAM PENYELESAIAN SENGKETA MEDIK ANTARA DOKTER DAN PASIEN - Muhammad Andriady Saidi Nasution; Beni Satria; Irwan Jasa Tarigan (Masyarakat Hukum Kesehatan Indonesia, 2022)
The legal relationship between doctors and patients is essentially a relationship that needs each other and is based on trust, but along the way, it is not impossible to end up in a medical dispute. The emergence of disputes that occur between doctors and patients is more often due to weaknesses in building effective communication which results in conflict between doctors and patients. The emergence of a conflict that leads to a dispute does not need to occur if both parties understand their position and position both from a medical and legal perspective through a good communication network, mutual respect and mutual trust. And if finally there is a medical dispute between the two parties, both doctors and patients, legal communication should be put forward such as mediation to resolve medical disputes that occur. Thus, mediation as legal communication in the resolution of medical disputes requires effective communication efforts by optimizing the value of a win-win solution between the disputing parties, both from the doctor and the patient, in achieving the goal of resolving medical disputes, especially outside the court (non-litigation mediation).